Optimization of breast treatment planning towards lower dose rate: A Monte Carlo simulation study. (2023) - Khorshidi, Abdollah; Ashoor, Mansour; Abdollahi, Ahmad
Abstract: Background: The inclusive symptom of breast cancer is a new mass or lump. Breast tumors may be a participation of dissimilar types or combination of invasive and in situ cancer. The positron emitting radionuclides may be employed to treat the breast. Methods: The various configurations of breast may be optimized to decrease the absorbed radiation dose, since the average glandular dose is regularly utilized as a criterion in radiation-risk detection. In this study, two configurations in cubic-rectangular (CR) and cylindrical-conical (CC) sketches along with appropriate assumptions were modelled and simulated via Monte Carlo technique, and the acquired dose rate (DR) values were compared. Results: The amounts of scattering and absorption cross sections of radiations next to the DR value reduced as the height of the CR sketch decreases. The mean dose rate value in the CR sketch reduced by 96.83% compared to that in the CC sketch. Additionally, raising the distance from the nipple (or raising the depth) reduced the DR values for both configurations. While the source of positron emitter was close to the right breast, the relative difference of the DR values between two sketches had major influence, for the CR outline which was high at the lower depths, and decreased linearly by increasing the depth. The accumulated DR value reduced severely in the CR sketch rather than the CC one. Conclusion: This study may be helpful to inspect deformed breast tissue in treatment planning. Highlights: Two deformations of the breast configuration were simulated to evaluate dose rate. A positron source was propagating the front and end of the breast. The dose rate as a function of depth from nipple was estimated for both deformed breasts.